Cardiac toxicity of EGFR – 3rd generation TKI in patients with metastatic non-small cell lung cancer. Case report and literature data update - Neagu, Andrei; Zaharia, Andreea-Eliza; Mihalache, Tiberiu; Goroftei, Larisa; Ilie, Lacramioara; Grigore, Ionica; Raileanu, Cosmin Raducu; Leu, Sorin; Matei, Madalina-Nicoleta; Rebegea, Laura-Florentina (Technium BioChemMed, 2022)
Purpose: The incidence of bronchopulmonary cancer has increased significantly in recent decades, especially in developed countries, and today it is the leading cause of death in men and the 3rd in women. The toxicities of tyrosine kinase inhibitor therapy are varied, with cardiac toxicities at the top of the pyramid. Because of the occurrence of these toxicities, depending on their intensity, the dose must be reduced or even treatment stopped. Patient and method: We present the case of a 72-year-old patient, diagnosed in 2019 with non-small bronchopulmonary neoplasm with histology of adenocarcinoma with EGFR mutation, stage IV. Results: In the oncology committee, it is decided to start targeted therapy with tyrosine kinase inhibitors of the first generation, Erlotinib, with a partial response to the treatment in the imaging evaluations, continued treatment until November 2020 when the T790M resistance mutation is detected. According to the new NCCN guidelines, therapy with the third-generation EGFR-TKI, Osimertinib, is initiated. In September 2021, the patient developed a non-ischemic acute antero-septal myocardial infarction that was complicated by LV apical aneurysm and severe LV systolic dysfunction, associated with therapy with tyrosine kinase inhibitors. Osimertinib treatment is stopped and third-line treatment with Vinorelbine is initiated. Conclusions: Investigation and permanent monitoring of patients, in treatment with 3rd generation tyrosine kinase inhibitors, who may develop cardiac toxicities, but also a good management of these toxicities, lead to both increased survival and improved status of performance.